(untitled) (Research, Society and Development, 2022)
Considering that several factors can influence the sowing process. The objective was to evaluate the energetic and operational performance of the tractor-seeder-fertilizer set in corn sowing as a function of two furrower mechanisms and four soil coverings. The study was carried out at the Agricultural Engineering Department of the Federal University of Ceará - Campus do Pici. The experimental design was in randomized blocks, the treatments consisted of two furrowing mechanisms (disc and shank) and four soil coverings (sunn hemp, sorghum, mombasa grass and uncovered soil) with four replications. The following variables were analyzed: force and power in the drawbar, mobilized area, depth of action of the furrower mechanisms, specific operational resistance, displacement speed, operational field capacity, skidding of the front and rear wheels of the tractor, slippage of the wheel of the seeder-fertilizer, hourly fuel consumption, operational consumption, specific consumption and consumption per mobilized area. The mobilized area was the same for the two types of furrowing mechanisms. The shank type furrower mechanism demanded greater strength and power from the tractor-seeder-fertilizer set and presented larger depth of action, which provided lower displacement speed. Regarding the furrower mechanisms for hourly consumption and operational consumption, there was no statistical difference. Cover plants do not influence the energy and operational performance of the tractor-seeder-fertilizer set, except for slippage of the wheel of the seeder-fertilizer. The disc type furrower mechanism provides better operational and energy performance for the tractor-seeder-fertilizer set, except for specific consumption and specific consumption per mobilized area.